2020
DOI: 10.1029/2019jd032098
|View full text |Cite
|
Sign up to set email alerts
|

Origin of an Uncommon Multiple‐Stroke Positive Cloud‐to‐Ground Lightning Flash With Different Terminations

Abstract: An uncommon three‐stroke positive cloud‐to‐ground (+CG) lightning flash was observed by synchronous multifrequency radiation sensors, and the three‐dimensional development of the channel was carefully mapped. Results show that three positive strokes grounded at different points approximately 4–8 km apart and time intervals between neighboring +CG strokes were 85 and 222 ms, respectively. This +CG flash was preceded by an intracloud (IC) discharge. The locations of the termination points on the ground were just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
(57 reference statements)
2
29
0
Order By: Relevance
“…Excluding some subsequent strokes with extremely small time differences from previous strokes (Figure 8) and also considering the fact that in some cases the location results are not good enough to make a correct determination of the processes before the positive strokes, we believe that for most subsequent strokes in MS +CG flashes, positive leaders originate from in‐cloud negative channels. This conclusion is also consistent with the recent observation of a MS +CG flash by Yuan et al (2020).…”
Section: Inferences On Origins Of Positive Leaders For First and Subssupporting
confidence: 94%
See 1 more Smart Citation
“…Excluding some subsequent strokes with extremely small time differences from previous strokes (Figure 8) and also considering the fact that in some cases the location results are not good enough to make a correct determination of the processes before the positive strokes, we believe that for most subsequent strokes in MS +CG flashes, positive leaders originate from in‐cloud negative channels. This conclusion is also consistent with the recent observation of a MS +CG flash by Yuan et al (2020).…”
Section: Inferences On Origins Of Positive Leaders For First and Subssupporting
confidence: 94%
“…In this mechanism, the head of the defunct branch corresponds to the point with 0 distance in Figures 13a–13d. This mechanism is also consistent with the report by Yuan et al (2020) that a positive leader initiated from a decayed negative leader branch.…”
Section: Inferences On Origins Of Positive Leaders For First and Subssupporting
confidence: 93%
“…Similarly, our fast antenna detected no distinct VLF-VHF radiation during the propagation of the downward positive leader in this case. However, the ripple-like stepped pulses on the waveform of fast E-field change frequently appeared at about 1 ms before a +RS, as referred to in previous studies (Kong et al, 2015;Nag & Rakov, 2012;Yuan et al, 2020). For now, it is unknown which physical process produced the LF/VLF radiation just 1 ms before a +RS.…”
Section: Characteristics Of Two Kinds Of Side Discharges From the Negative Leadermentioning
confidence: 71%
“…Later, Nag and Rakov (2012) presented a sketch map of the inferred process that the downward positive leader initiated from the cutoff point of a negative leader, then van der Velde et al (2014) proposed a similar scenario after investigating 35 sprite-producing +CG flashes. Recent studies based on the LF 3D mapping technique have found that the occurrence of uncommon multiple-stroke +CG lightning with different terminations is also related to the downward positive leader developing from the horizontal negative channel (Wu et al, 2020b;Yuan et al, 2020). Furthermore, bipolar lightning, containing upward and downward CG lightning, was also related to the occurrence of such kind of side discharges, which play an important role in reversing the polarity of the charge into the ground (Rakov, 2003;Saba et al, 2013).…”
mentioning
confidence: 99%
“…The downward positive leader in our case was a bifurcation of the positive polarity branch of the IC discharge. In fact, the +CG leader could emanate from IC discharges of either polarity (Saba et al., 2009; Yuan et al., 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%